Antiplasmodial Activity of Hydroalcoholic Extract from Jucá (Libidibia ferrea) Pods - Francisco Flávio Vieira de Assis; José Sousa de Almeida Junior; Tânia Mara Pires Moraes; Fernando de Pilla Varotti; Camila Castilho Moraes; Adilson Sartoratto; Waldiney Pires Moraes; Antonio Humberto Hamad Minervino (MDPI AG, 2023)
Malaria is an infectious and parasitic disease caused by protozoa of the genus Plasmodium, which affects millions of people in tropical and subtropical areas. Recently, there have been multiple reports of drug resistance in Plasmodium populations, leading to the search for potential new active compounds against the parasite. Thus, we aimed to evaluate the in vitro antiplasmodial activity and cytotoxicity of the hydroalcoholic extract of Jucá (Libidibia ferrea) in serial concentrations. Jucá was used in the form of a freeze-dried hydroalcoholic extract. For the cytotoxicity assay, the(3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) method with the WI-26VA4 human cell line was used. For the antiplasmodial activity, Plasmodium falciparum synchronized cultures were treated with serial concentrations (0.2 to 50 μg/mL) of the Jucá extract. In terms of the chemical composition of the Jucá extract, gas chromatography coupled to mass spectrometry measurements revealed the main compounds as ellagic acid, valoneic acid dilactone, gallotannin, and gallic acid. The Jucá hydroalcoholic extract did not show cytotoxic activity per MTT, with an IC50 value greater than 100 µg/mL. Regarding the antiplasmodial activity, the Jucá extract presented an IC50 of 11.10 µg/mL with a selective index of nine. Because of its antiplasmodial activity at the tested concentrations and low toxicity, the Jucá extract is presented as a candidate for herbal medicine in the treatment of malaria. To the best of our knowledge, this is the first report of antiplasmodial activity in Jucá.